The Influence of Green Marketing Mix on the Purchasing Decision of The Body Shop Products at Lippo Plaza Jember - Putrisari, Teti; Azhad, Muhamad Naely; Samsuryaningrum, Ira Puspitadewi (CV. Ulil Albab Corp, 2024)
Green marketing, marketing is done by combining environmental concerns needed by consumers in every marketing activity carried out by the company. The purpose of this study is to determine the effect of green marketing mix on The Body Shop Lippo Plaza Jember products. The results showed that this green marketing mix simultaneously influenced the purchase decision of The Body Shop products at Lippo Plaza Jember. This shows that the better the green marketing mix strategy at The Body Shop Jember, the more purchasing decisions made by consumers will be to buy products at The Body Shop Jember.